Application of TOPSIS method in assessment of the best learning comunication media for elementary school students - Pramesti, Pricilia Intan; Prasetya, Julian Rienaldi; Dwi Lestari, Tiffany Ovilia; Khoirunnisa, Miftakhul Gina (SHM Publisher, 2022)
The spread of the Covid-19 virus that occurred so quickly and occurred almost all over the world caused the implementation of activities to be carried out online, including learning activities. The main thing that can help the online learning process is technology, especially communication technology. Commonly used communication media to assist the online learning process include Whatsapp, school e-learning Web, Youtube, Zoom, and Google Meet. Of course, every communication media used has advantages and disadvantages. This study aims to determine the best learning communication media using the TOPSIS method to assist users in choosing the best communication media for elementary school students based on the criteria for easy use and maintenance, completeness of features, quota requirements, understanding obtained, and the ability to re-access information. The results of this study indicate that the best communication media for elementary school student learning is the Whatsapp application. In addition, this research also produces a simple excel-based TOPSIS program that can be used by educators to determine what application is right for use in the learning process because many criteria are considered by an educator to determine the application